Direct trifluoromethylation of imidazoheterocycles in a recyclable medium at room temperature1. Issue 38 (30th April 2015) - Ji, Xiao-Ming; Wei, Liang; Chen, Fan; Tang, Ri-Yuan
<x xml:space="preserve">Abstract</x> Regioselective C–H trifluoromethylation of imidazoheterocycles with Langlois' reagent in a recyclable mixed medium of 1-butyl-3-methylimidazoliumtetrafluoroborate ([Bmim]BF4) and water at room temperature has been developed.